Testing The Antibacterial Activity Of The Ethanol Extract Of Duku Fruit (Lansium Domesticum Corr) Peel Against Salmonella Typhi Bacteria - Dewi Pratiwi (Institut Kesehatan Medistra Lubuk Pakam, 2023)
One of the diseases that arise due to infection with pathogenic bacteria is typhoid fever. Typhoid is an infectious disease that is transmitted through the bacterium Salmonella typhi. One of the plants that can be used as an antibacterial is duku fruit skin. Duku fruit skin leaves were extracted by maceration with 96% ethanol as solvent. The extract obtained was s screened for phytochemicals to see what secondary metabolites were found in duku fruit skin leaves. This study consisted of 4 treatment groups, namely extract concentration 25%, 50%, 75%, positive control (Kloramfenikol), and negative control (aquadest), with 3 repetitions to minimize the possibility of data errors in the study. Antibacterial activity test was carried out using the Kirby-Bauer disc diffusion method. The ethanolic extract of duku fruit skin leaves contains alkaloid, flavonoid, saponin, tanin, and triterpenoid. The ethanolic extract of duku fruit skin leaves had antibacterial activity at concentrations of 25%, 50%, and 75% against Salmonella typhi with inhibition zone diameters of 10,22 mm, 11,94 mm, 13,63 mm, respectively. The results of unvariate data analysis showed that the ethanolic extract of duku fruit skin leaves had antibacterial activity against Salmonella typhi and the higher the concentration, the wider the inhibition zone formed.